Determination of PAR4 numbers on the surface of human platelets: no effect of the single nucleotide polymorphism rs773902. (3rd October 2021) - Li, Simeng; Tarlac, Volga; Christanto, Roberto B. I.; French, Shauna L.; Hamilton, Justin R.
Abstract: The thrombin receptor, protease-activated receptor 4 (PAR4), is important for platelet activation and is the target of emerging anti-thrombotic drugs. A frequently occurring single nucleotide polymorphism (SNP; rs773902) causes a function-altering PAR4 sequence variant (NC_000019.10:p.Ala120Thr), whereby platelets from Thr120-expressing individuals are hyper-responsive to PAR4 agonists and hypo-responsive to some PAR4 antagonists than platelets from Ala120-expressing individuals. This altered pharmacology may impact PAR4 inhibitor development, yet the underlying mechanism(s) remain unknown. We tested whether PAR4 surface expression contributes to the altered receptor function. Quantitative flow cytometry was used to determine the absolute number of PAR4 on platelets from individuals subsequently genotyped at rs773902. We detected 539 ± 311 PAR4 per platelet (mean ± SD, n = 84 ). This number was not different across rs773902 genotypes. This first determination of cellular PAR4 numbers indicates variations in platelet surface expression do not explain the altered pharmacology of the rs773902 PAR4 sequence variant.